2002
DOI: 10.1007/s00259-002-0848-8
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in thyroid disease

Abstract: The autoimmune thyroid diseases, Graves' disease and autoimmune hypothyroidism, represent the two ends of a disease spectrum where an immune response is directed against the thyroid gland. In Graves' disease, antibodies directed against the thyrotropin receptor (TSH-R) lead to the development of glandular overactivity, while in autoimmune hypothyroidism, cell-mediated and humoral thyroid injury leads to destruction of thyroid tissue and thyroid hormone deficiency. The mechanisms by which these diseases develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 76 publications
0
19
0
2
Order By: Relevance
“…The definitive etiology for this breakdown in immune tolerance remains elusive, although both genetic and environmental factors have been postulated (1)(2)(3)(4)(5). The only consistent associations with AITD, however, are with the human leukocyte antigen (HLA) class II region on chromosome 6p21 (specifically in the DR3 region) and the cytotoxic T lymphocyte-associated-4 region on chromosome 2q33 (2-4, 6, 7).…”
Section: T He Autoimmune Thyroid Diseases (Aitds)mentioning
confidence: 95%
“…The definitive etiology for this breakdown in immune tolerance remains elusive, although both genetic and environmental factors have been postulated (1)(2)(3)(4)(5). The only consistent associations with AITD, however, are with the human leukocyte antigen (HLA) class II region on chromosome 6p21 (specifically in the DR3 region) and the cytotoxic T lymphocyte-associated-4 region on chromosome 2q33 (2-4, 6, 7).…”
Section: T He Autoimmune Thyroid Diseases (Aitds)mentioning
confidence: 95%
“…A study of twin cohorts indicated that around 80% of the susceptibility to AITD is the result of genetic factors [5]. Among several different chromosomal regions and candidate genes that are believed to be associated with AITD [6,7], the gene for cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) on chromosome 2q33 is a strong genetic factor in susceptibility to AITD [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Because AITD have a multifactorial and complex genetic etiology, the identification of susceptibility genes is difficult. Based on experimental and functional analyses, several genes have been proposed as candidate, susceptibility, or immunoregulatory genes for AITD (5). Genome wide screening and linkage analyses have identified several chromosomal regions which are linked to AITD (3).…”
Section: Introductionmentioning
confidence: 99%